Analysis and design of object-oriented program understanding system. - Mohd Sani, Nor Fazlida; Mohd. Zin, Abdullah; Idris, Sufian (2009)
Programming is the most difficult task to most computer sciences students. They always faces problem to write and to understand the program codes. There are lots of exercises is been given to students for practice on writing a program code. But those students still faces problem on understanding the programming codes while written it. The purpose of this paper is to present the model and the developed system that can help students to understand the programming codes. It is a program understanding system for an object-oriented programming language using the plan base approach named CONCEIVER++. In this paper will describe the design and implementation of two main modules of this system, the understanding and editor modules.